2016
DOI: 10.1111/mmi.13359
|View full text |Cite
|
Sign up to set email alerts
|

Type IV traffic ATPase TrwD as molecular target to inhibit bacterial conjugation

Abstract: Summary Bacterial conjugation is the main mechanism responsible for the dissemination of antibiotic resistance genes. Hence, the search for specific conjugation inhibitors is paramount in the fight against the spread of these genes. In this pursuit, unsaturated fatty acids have been found to specifically inhibit bacterial conjugation. Despite the growing interest on these compounds, their mode of action and their specific target remain unknown. Here, we identified TrwD, a Type IV secretion traffic ATPase, as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 52 publications
2
70
0
Order By: Relevance
“…Therefore, our study reveals an unprecedented level of conformational complexity, which might be exploited functionally at many different levels. Such a large conformational spectrum might be the reason why it has been difficult to design VirB11‐targetting drugs . The novel insights we now provide might prove decisive in progressing these efforts to a successful conclusion.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, our study reveals an unprecedented level of conformational complexity, which might be exploited functionally at many different levels. Such a large conformational spectrum might be the reason why it has been difficult to design VirB11‐targetting drugs . The novel insights we now provide might prove decisive in progressing these efforts to a successful conclusion.…”
Section: Resultsmentioning
confidence: 98%
“…Experiments have also identified unsaturated and 2‐alkynoic fatty acids as inhibitors of conjugation. These target the ATPase associated with the T4SS (Ripoll‐Rozada et al, ). Tanzawaic acids show particular promise having relatively broad host‐range against different types of plasmid conjugation while being relatively nontoxic (to bacteria, fungi, and human cells; Getino et al, ).…”
Section: Inhibiting the Plasmidmentioning
confidence: 99%
“…This "cleaved complex" is characterized by the presence of DNA breaks, which have been crystallized and found to have the fluoroquinolone C-7 ring system facing the GyrB subunit (Mustaev et al, 2014). In the case of 1, it was demonstrated that this compound displayed COIN activity in E. coli by the inhibition of TrwD ATPase (Garcia-Cazorla et al, 2018;Getino et al, 2015;Ripoll-Rozada et al, 2016). It was shown that 1 binds to the N-terminal domain (NTD) and the linker region of TrwD ATPase resulting in the restriction of the movement of the NTD over the catalytic domain (CTD), which would result in a reduction of the TrwD ATPase activity (Ripoll-Rozada et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of 1, it was demonstrated that this compound displayed COIN activity in E. coli by the inhibition of TrwD ATPase (Garcia-Cazorla et al, 2018;Getino et al, 2015;Ripoll-Rozada et al, 2016). It was shown that 1 binds to the N-terminal domain (NTD) and the linker region of TrwD ATPase resulting in the restriction of the movement of the NTD over the catalytic domain (CTD), which would result in a reduction of the TrwD ATPase activity (Ripoll-Rozada et al, 2016). These findings are revealing because S. aureus DNA gyrase contains a GyrB subunit, an enzymatic region that has ATPase activity (Eakin et al, 2012;Fàbrega et al, 2009), which could explain the observed inhibitory activity of 1 toward the S. aureus DNA gyrase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation